Librarians, historians, and new opportunities for discourse a guide for Clio's helpers - Kitchens, Joel D. (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2012)
This book stimulates informed dialogue between librarians and historians regarding the changing nature of history and the resultant needs for a wider variety of collections and library services, including inter-library loan, library instruction, outreach, and reference.